2018
DOI: 10.1002/ajpa.23735
|View full text |Cite
|
Sign up to set email alerts
|

Impact of population‐specific dental development on age estimation using dental atlases

Abstract: ObjectivesThe steady development and subsequent eruption of the dentition is particularly useful for the estimation of age in juveniles. There are few studies that examine and test methods on a population‐diverse sample. Our goal is to test the Ubelaker () and London Atlas (2010) dental charts on a sample representing several different population backgrounds to infer if refinement for population‐specific standards should be developed.Materials and methodsThe first and second authors examined panoramic radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Although the classification of these individuals as non-adults is reliable, the age ranges provided may not reflect their "true" chronological age. This is because population-specific and period-specific dental development criteria for this geographic region, population, and archaeological period do not exist and were therefore not used (Hillson 2005, 211;Adams et al 2018;Smith 2020). Moreover, the exact time and rate at which individual teeth undergo the mineralisation process has been shown to vary both between and within individuals, thereby reducing the effectiveness of tooth formation for estimating the age-at-death for samples originating from an unstudied archaeological population (Montgomery 2010;Hillson 2005;Evans, Chenery, and Fitzpatrick 2006;Akkus et al 2016;Adams et al 2018;Esan, Mothupi, and Schepartz 2018).…”
Section: The Human Remains From Harlaamentioning
confidence: 99%
See 1 more Smart Citation
“…Although the classification of these individuals as non-adults is reliable, the age ranges provided may not reflect their "true" chronological age. This is because population-specific and period-specific dental development criteria for this geographic region, population, and archaeological period do not exist and were therefore not used (Hillson 2005, 211;Adams et al 2018;Smith 2020). Moreover, the exact time and rate at which individual teeth undergo the mineralisation process has been shown to vary both between and within individuals, thereby reducing the effectiveness of tooth formation for estimating the age-at-death for samples originating from an unstudied archaeological population (Montgomery 2010;Hillson 2005;Evans, Chenery, and Fitzpatrick 2006;Akkus et al 2016;Adams et al 2018;Esan, Mothupi, and Schepartz 2018).…”
Section: The Human Remains From Harlaamentioning
confidence: 99%
“…Enamel mineralisation is a complex two-stage process resulting in a degree of time-averaging that varies in duration in different places of the same tooth, and in two different teeth that formed simultaneously in the same individual (Montgomery 2010). Additionally, individual molar elements mineralise at different speeds in different individuals with important differences between males and females (Adams et al 2018;Esan, Mothupi, and Schepartz 2018;White and Folkens 2005;Hillson 2005, 210-214;Demirjiajn and Levesque 1980). This means that the mineralisation period in human teeth can only be stated approximately, which complicates the process of aligning isotopic data measured at high resolution by laser ablation from multiple teeth from the same individual.…”
Section: Comparisons Between Teeth Sampled From the Same Individualmentioning
confidence: 99%
“…Matsuoka et al found high expression of VEGF in RPE cells and vascular endothelial cells in the eyes among patients with PCVs (24). By directly suppressing the VEGF highly expressed among PCV patients, anti-VEGF agents were confirmed to distinctly improve their vision, and decrease the exudation and the thickness of the fovea (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals evaluated ranged in age from fetal to 19 years (for examples of the range, see Adams et al, 2019; Beyer‐Olsen & Risnes, 1994; Brickley et al, 2018; Cowgill, 2007; Gaither, 2012; Geber, 2014; Newman et al, 2019; Newman & Gowland, 2017). Smaller studies (family cemeteries or comingled burials) assessed children of different ages.…”
Section: Literature Review: Resultsmentioning
confidence: 99%
“…The remaining two studies with 500+ individuals used radiographs to assess findings identified first on macroscopic examination (Brickley et al, 2018;Verlinden & Lewis, 2015). Individuals evaluated ranged in age from fetal to 19 years (for examples of the range, see Adams et al, 2019;Beyer-Olsen & Risnes, 1994;Brickley et al, 2018;Cowgill, 2007;Gaither, 2012;Geber, 2014;Newman et al, 2019;Newman & Gowland, 2017).…”
Section: Overview and Descriptive Statisticsmentioning
confidence: 99%